Early metabolic response to chemoradiotherapy by interim FDG PET/CT is associated with better overall survival and histological response in esophageal cancers. Issue 6 (June 2019) - Hammoudi, N.; Hennequin, C.; Vercellino, L.; Costantini, A.; Valverde, A.; Cattan, P.; Quéro, L.
Abstract: Background: Early assessment of response to neoadjuvant chemoradiotherapy (CRT) is crucial in determining the most suitable treatment strategy in locally advanced oesophageal cancer (LAEC). Aims: We evaluated the impact of early metabolic response during CRT on overall survival (OS) and histological response. Methods: Patients with biopsy-proven oesophageal carcinoma underwent FDG PET/CT with evaluation of the standardized uptake value (SUV) before any treatment and during CRT after 20 Gy. Results: 116 patients (Male: 66.4%, Median age: 63; squamous cell carcinomas (SCC): 70%) met inclusion criteria. Median OS was 21.7 months. There was a significant positive correlation between interim metabolic response and OS. In multivariate analysis, only metabolic response using the 50% cut-off value remained significantly associated with OS (IC95% = 0.28–0.73; p = 0.001). In this statistical analysis, surgery (p = 0.007) and T stage (p = 0.023) were also correlated with OS. There was a significant correlation between early metabolic response and local recurrence (Chi-squared test p = 0.0001). Conclusions: Early metabolic response using FDG PET/CT is associated with better OS, disease-free survival, local control and pathological response in patients treated by CRT for LAEC.